Generation of synthetic rainfall for the tropical region - Sia, Sheau Yunn. (2009)
A network of 13 rain gauges has been set up on the campus of NTU. The methods of rainfall recording and analysis are event-based and follow the procedure proposed by Tan and Chiew (1991). This study coupled the event-based method of rainfall recording and analysis with a model to generate synthetic rainfall time-series for the tropical region.